Performance of Various Speckle Reduction Filters on Synthetic Aperture Radar Image - Santoso, Ardhi W.; Pebrianti, Dwi; Bayuaji, Luhur; Jasni, Mohamad Zain (IEEE, 2015)
Synthetic Aperture Radar (SAR) image with its advantages, becoming popular than the optical image. However, the speckle in causes difficulties in the interpretation and analysis during image processing. Thus, before the SAR images are used, speckle noise reduction is necessary. The ideal speckle filter has the main goal of reducing speckle noise without losing the information, content, and preserve the edges and features. Various noise filters have been designed for different purposes and different capacities. In this study, we discuss four filters, namely Lee, Frost, Median and Mean filter. We are analyzing quality parameter and comparing statistic performance of Lee, Frost, Mean and Median filters for SAR sample data. The results show MSE, PSNR, SNR, and AD value that generate by Frost filter performs better than the other filter. And from visual interpretation of the de-speckle image that filtered with Frost filter, show sharpen edge and preserved texture.